First Report of Botryosphaeria dothidea (Moug. : Fr.) Ces. & De Not. (Anamorph: Fusicoccum aesculi Corda) on Jatropha curcas L. in China - Yue-kai, Wu; Guo-teng, Ou; Jin-yong, Yu; Jian-chang, Sun (Journal of Tropical Agriculture, 2012)
In Luodian County of Guizhou Province, P.R. China, the biofuel crop Jatropha curcas L. is prone to many diseases, of which stem and branch canker is one of the most serious diseases. In the field, the disease shows different symptoms and usually results in the death of seedlings, or death of branches and stems resulting in tree decline. Most fungal isolates from the infected stems have similar colonial characteristics and microscopic features, and are pathogenic to J. curcas as validated by the pathogenicity test. Based on the results of morphological study and current taxonomic status of the related fungal group, the fungus that causes the canker disease of J. curcas in Luodian county of China is identified as Botryosphaeria dothidea (Moug. : Fr.) Ces. & De Not., and the anamorph is Fusicoccum aesculi Corda.